A model for psychophysiological regeneration of elite team athletes - Venter, R. E. (University Stellenbosch, 2008)
There is general consensus that athletes, striving to compete and perform at the highest level, should optimally balance training and competition stress with adequate regeneration. Although a well-planned training programme is of utmost importance, the time between training sessions and competitions is critical for the modern-day athlete. It is suggested that athletes should apply a variety of recovery methods to enhance the regeneration process. Although team sport is a popular entity throughout the world, there is limited published research on the regeneration process in team athletes and recovery methods to enhance the regeneration process. The aim of this study was to develop a model that could serve as a guideline for the regeneration of team athletes within the South African context. Two phases were involved in the process of developing a model. Phase one involved a research of literature in order to assess which strategies can be implemented for athletic regeneration, and what information team athletes are given for regeneration. The second phase involved an investigation into the recovery strategies that are currently used for regeneration by elite South African team players during the competitive phase of the year. Research questions focused on the recovery methods used by players, the perceived importance of various recovery methods to the players, and the relationship between sport and level of participation in the use of recovery strategies. This study did not attempt to assess the knowledge of the players on recovery methods.